Common features of spontaneity and stream of consciousness in prose, poetry and song lyrics - Януш, Олег Богданович (Київський національний університет імені Тараса Шевченка, 2025)
The article deals with basic techniques and means of expression in literature like spontaneity and stream of consciousness. Taking into consideration different literary devices of expressing and depicting thoughts, experiences, moods, the author focuses on those two phenomena in language of prose, poetry, music lyrics of well-known authors of the 20th century. The author has deeply studied different researches on the topic, fulfilled particularly by prominent philosophers and psychologists of 19th and 20th centuries. Spontaneity is defined as human quality, which determines as well as influences the reaction on changing of certainty or unusual lifetime conditions. Within this connection the author mentions the theory for researching concepts of spontaneity and creativity. Attention is paid to spontaneity and creativity as different categories, but strategically linked. After all, he claims that a high degree of spontaneity does not mean creativity. Both categories can be applied in literature or song writing, in a skillful manner in particular. The author proposes the definition of the phenomenon of stream of consciousness as a stylistic device for the linguistic organization of the written text, which shows the complicated process of mental thinking with deep concentration on thoughts and feelings. Also, it is necessary to add that some authors determine several parts of this process (the stream): the pre-impulse to think, the thought, and the external circumstances at present time, that is simultaneously, evoking some reactions and changing the thinking process, closely connecting it with the concept of spontaneous poetry and prose. The attention has been emphasized on the spiritual life of the individual, the spontaneity of the emergence of thoughts and images, combination of the conscious and the unconscious, the rational and the sensual, increased emotionality, etc. Special attention is also paid to spontaneity and stream of consciousness as essential concepts in order to differentiate synonymic of lexemes denoting behavioral traits of a person's character, which look alike at first glance only: impulsivity, improvisation and quick burst of emotionality. These characteristics of human actions have also been distinguished and differentiated. As a result of analysis of both concepts, the author concludes to support the idea of common features for spontaneity and stream of consciousness, taking into account that in literature these concepts are implemented in poetic texts as literary devices. That is why the necessity to explore literary works in further scientific investigations is signified by the represented research.

У статті розглядаються такі основні прийоми та засоби вираження в літературі, як спонтанність і потік свідомості. Зважаючи на різні літературні засоби вербалізації думок, переживань, настроїв, автор акцентує увагу на цих двох явищах у мові прози, поезії, музичної лірики відомих авторів ХХ століття. Автор проаналізував сучасні дослідження з цієї проблематики, зокрема філософами та психологами XIX – XX століть. Спонтанність розуміється як характеристика людини, яка впливає на зміну визначеності / невизначеності обставин життя. У цьому зв'язку автор аналізує теорію понять спонтанності та креативності. Увага приділяється спонтанності та креативності як різним категоріям, але стратегічно пов'язаним. Стверджується, що високий ступінь спонтанності не означає креативності. Обидві категорії є актуальними в літературознавстві та в цілому в гуманітаристиці, а також виявляють свої інтенції в художній творчості. Автор розглядає феномен потоку свідомості як стилістичний прийом мовної організації художнього тексту, який виявляє складний процес мислення з глибокою концентрацією на думках і почуттях. Зауважено й на тому, що деякі автори виділяють кілька етапів цього процесу: передімпульс до мислення, думка та зовнішні обставини в конкретний час, тобто одночасно йдеться про певні реакції та зміни у процесі мислення, тісно пов'язуючи його з поняттям спонтанної поезії та прози. Акцентовано увагу на духовному житті особистості, особливостях думок і образів, поєднанні свідомого і несвідомого, раціонального і чуттєвого, підвищеній емоційності в художньому слові тощо. Також особлива увага приділяється спонтанності та потоку свідомості як суттєвим поняттям для розмежування синонімічних лише на перший погляд схожих лексем, що позначають поведінкові риси характеру людини: імпульсивність, імпровізація та стрімкий сплеск емоційності. Ці характеристики дій людини також проаналізовані у статті та диференційовані. Схарактеризувавши названі поняття, автор приходить до висновку про спільні риси спонтанності та потоку свідомості, що в поетичних текстах є формами творення художнього слова. Тому репрезентоване дослідження свідчить про перспективу щодо необхідності аналізу описаних явищ у подальших наукових розвідках.
Спільні риси спонтaнності та потоку свідомості у прозі, поезії та текстах пісень
Keywords: spontaneity; stream of consciousness; techniques; expression; artistic means; literary device.; спонтанність; потік свідомості; прийоми; виразність; художні засоби.